1987
DOI: 10.1128/jcm.25.9.1611-1622.1987
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency switching in Candida strains isolated from vaginitis patients

Abstract: High-frequency switching and strain variability at the site of infection was assessed in Il patients with acute Candida albicans vaginitis. By cloning cells directly from the site of infection, it was demonstrated that 4 of the 11 isolates contained multiple-switch phenotypes at the site of infection and that 9 of the 11 isolates were in a high-frequency mode of switching (10-2 to 10-3). Isolates could be separated into four general categories of switching repertoires. To demonstrate that multiple phenotypes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0
6

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(135 citation statements)
references
References 16 publications
1
128
0
6
Order By: Relevance
“…These include pregnancy, use of oral contraceptives or antibiotics and diabetes mellitus. 3,5 Candida albicans has several virulence factors, including hyphal formation, 6 phenotypic switching, [7][8][9] secretion of hydrolytic enzymes 10,11 and adhesion to epithelial cells. Members of the ALS gene family encode cell-wall glycoproteins, some of which are implicated in the adhesion to host surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…These include pregnancy, use of oral contraceptives or antibiotics and diabetes mellitus. 3,5 Candida albicans has several virulence factors, including hyphal formation, 6 phenotypic switching, [7][8][9] secretion of hydrolytic enzymes 10,11 and adhesion to epithelial cells. Members of the ALS gene family encode cell-wall glycoproteins, some of which are implicated in the adhesion to host surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…8 Many studies have shown a much higher frequency of hyphae phenotype of C. albicans in infected sites. 1,6,9 Biofilms, which are heterogeneous communities of microorganisms growing on a solid substrate, are formed by C. albicans. 10 Candida albicans organised in biofilms has been reported to be up to 1000 times more resistant to antifungal drugs compared with their planktonic form.…”
Section: Introductionmentioning
confidence: 99%
“…Both the blastospore and germ tube forms of C. albicans (7,18), as well as other morphological forms of C albicans (25), are likely to be virulent if this organism gains more than its carrier status foothold inside its ecological niche. The germ tube form has, in addition, been shown to enhance the virulence of the organism in vaginal candidiasis animal model systems (24) and might be expected to play a similar role in oral candidiasis.…”
Section: Resultsmentioning
confidence: 99%